2020
DOI: 10.3390/ijerph17020449
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Just Addictive People That Make Addictive Videos”: Children’s Understanding of and Attitudes towards Influencer Marketing of Food and Beverages by YouTube Video Bloggers

Abstract: Exposure to influencer marketing of foods and beverages high in fat, sugar, and/or salt (HFSS) increases children’s immediate intake. This study qualitatively explored children’s understanding of, and attitudes towards, this marketing, to elucidate potential mechanisms through which exposure affects behavior. In six focus groups (n = 4) children (10–11 years) were shown a YouTube video featuring influencer marketing of an HFSS product. Inductive thematic analysis identified six themes from children’s discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 79 publications
(159 reference statements)
4
46
0
1
Order By: Relevance
“…The findings are consistent with consumer research that has demonstrated the importance of examining how marketing shapes and reinforces attitudes towards HFSS products/brands [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], in addition to research examining the associations between the volume and frequency of marketing exposure and dietary outcomes [1]. The findings are also consistent with suggestions that some young people may be more susceptible to the persuasive intent of HFSS marketing.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The findings are consistent with consumer research that has demonstrated the importance of examining how marketing shapes and reinforces attitudes towards HFSS products/brands [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], in addition to research examining the associations between the volume and frequency of marketing exposure and dietary outcomes [1]. The findings are also consistent with suggestions that some young people may be more susceptible to the persuasive intent of HFSS marketing.…”
Section: Discussionsupporting
confidence: 84%
“…The eight reaction measures, albeit informed by focus groups [16] and existing research [46], are not exhaustive of all possible reactions. It is plausible that young people may have formed other opinions to the adverts (both positive and negative) that were not captured in the measures, and a more detailed understanding concerning appeal and interpretation could have been generated by showing creatives in qualitative research [15][16][17][18][19][20]. We also cannot determine to what extent, if at all, reactions were influenced by existing heuristics and attitudes towards the brands depicted (e.g., due to prior exposure to other forms of marketing).…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The popularity may result from vlogs being the most likely video genre to feature positive, neutral, and negative types of self-disclosure, and this may lead to more interesting content and a stronger para-social relationship between viewers and influencers (Ferchaud et al, 2018). Young consumers are motivated to watch vlogs because they provide entertainment, information, social validation of their own interests, and window into different yet highly interesting lives (Coates et al, 2020). They feel a strong attachment, intimacy, and even addiction to the influencers as young consumers perceive them to be more accessible, authentic, and similar than traditional celebrities (Coates et al, 2020).…”
Section: Introductionmentioning
confidence: 99%